The Relationships and Connections Between International and National Law - Skubiszewski, Krzysztof (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The paper is an English translation of Wzajemny stosunek i związki pomiędzy prawem międzynarodowym i prawem krajowym by Krzysztof Skubiszewski, published originally in Polish in “Ruch Prawniczy, Ekonomiczny i Socjologiczny” in 1986. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Department of Public International Law” devoted to the achievements of the representatives of the Poznań studies on international law.